A community-based cross-sectional study about the quality of life in postmenopausal women in rural Puducherry - R Sivapragasam; S Rajini; S Rajalakshmi; K Priyanga; V Rajesh; R Priyadharshini (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to assess the quality of life (QOL) of postmenopausal women, in the rural areas of Puducherry and to find the associated factors. Materials and Methods: A cross-sectional study was done in the rural field practicing area of SLIMS, Puducherry. The sample size was 172 based on the previous study, and simple random sampling technique was used. The women who were receiving hormonal treatment, having chronic illness and those who refused to participate were excluded from the study. The sociodemographic information and menopause-specific QOL questionnaire were used, and data were analyzed using the SPSS 21. Results: In this study, mean age of the postmenopausal women was 61 ± 7.5 years, 42.4% belonged to socioeconomic status (SES) Class IV. The prevalence of one or more symptoms of vasomotor, psychological, and sexual domains were 23.8%, 87%, and 68%, respectively. We found an association between SES and both vasomotor and psychological symptoms. Furthermore, age and psychological symptoms were associated. Conclusion: The menopause-related symptoms had a negative effect on the QOL of postmenopausal women. The study can help in creating awareness and also in helping in educating women for early identification of the frequent menopausal symptoms.